Materials for the dictionary of V.A. Zhukovsky’s poetic language - Zhatkin, Dmitry N.; Vasilyev, Nikolay L.; Stepkin, Igor R. (Universidade Estadual Paulista, 2021)
The research paper provides a detailed presentation of a new lexicographical project, aimed at continuing the developed series of alphabetical frequency dictionaries of Russian writers of the past, in particular, the poets of A.S.Pushkin’s galaxy, as well as his predecessors. The text corpus of the dictionary consists of all the known poetic works by V.A.Zhukovsky. The methodology for compiling this lexicographical reference book was tested in the process of creating our previous alphabetical frequency dictionaries of writers. The dictionary will incorporate three sections, i.e. the list of words, used in V.A.Zhukovsky’s poetic works (including lexical and phraseological foreignisms); the list of proper names, which one may find in his poetry; the rating of the most frequently used words (used no less than 10 times). The research paper provides an example of a fragment of the word list of the Dictionary of V.A.Zhukovsky’s Poetic Language, prepared on the basis of the conducted research.